Population Seasonality: Will They Stay or Will They Go? A Case Study of the Sogatella furcifera (Hemiptera: Delphacidae). Issue 1 (25th May 2015) - Ma, Mingyong; Wu, Shengwei; Peng, Zhaopu
Abstract : The whitebacked planthopper Sogatella furcifera (Horváth) (Hemiptera: Delphacidae) is one of the most destructive pests of rice in East and Southeast Asia. It is also a long-distance migratory insect and population size fluctuates frequently in these rice regions along the middle and lower Yangtze River. We analyzed the population seasonality of S. furcifera based on field surveys, light trap catching, and meteorological factors. We found that many S. furcifera were retained in local late rice in 2012, due to continuous rain and slightly windy weather conditions during the migration period. These results suggest that a new pattern of population fluctuation may occur where resident S. furcifera are dispersed into a single medium rice during harvest period, then rebound and thrive in late rice when there are suitable temperatures in September. Although the residency of S. furcifera in late rice fields in 2012 seems to be a special case, our findings suggest that S. furcifera exhibit a type of facultative migration. Our research also illuminates studies of the migration events of S. furcifera and benefits our understanding of the dynamics of S. furcifera in Hunan Province.